A study of emittance measurement at the ILC - Blair, G; Agapov, I; Carter, J; Deacon, L; Angal-Kalinin, D; Jenner, L; Ross, M; Seryi, A; Woodley, M (European Physical Society Accelerator Group (EPS-AG), 2006)
The measurement of the International Linear Collider (ILC) emittance in the ILC beam delivery system (BDS) is simulated. Estimates of statistical and machine-related errors are discussed and the implications for related diagnostics RandD are inferred. A simulation of the extraction of the laser-wire Compton signal is also presented.